Application of the international classification of functioning, disability, and health to disability assessment for older people in China - Zhao, Yuanping; Xie, Hong; Wang, Kun; Liu, Shouguo; Yan, Juan; Li, Jianan (Frontiers in Rehabilitation Sciences, 2024)
Background: In the previous research, the Disability Assessment Scale based on ICF had been constructed for LTC insurance in China. To apply this scale in further studies, it is essential to establish assessment standards for disability levels. Objective: To establish standardized disability classification criteria and identify the disability statuses and levels in older people. Methods: This is a cross-sectional study, in which 1,610 older individuals in 15 long-term care institutions in China were assessed by the disability assessment scale based on ICF. Cluster analysis was used for classification of the disability levels. Mean (SD) and median (IQR) were used to describe the scores for each item and each dimension. Results: The total scores of the disability assessment scale were classified into six disability levels. The overall disability level of the 1,610 participants was moderate-to-severe. The disability in the dimension of “self-care ability and activity” was the most obvious and severe. Conclusion: The Disability Assessment Scale is capable of identifying disability statuses and levels of older people, and it can serve as a valuable tool for investigating the disabilities among old people and for conducting cross-national comparisons of disability levels.